The use of isomeric testosterone dimers to explore allosteric effects in substrate binding to cytochrome P450 CYP3A4 - Denisov, Ilia G. (J Inorg Biochem, 2015)
Cytochrome P450 CYP3A4 is the main drug-metabolizing enzyme in the human liver, being responsible for oxidation of ~ 50% of all pharmaceuticals metabolized by human P450 enzymes. Possessing a relatively large substrate-binding pocket, it can simultaneously bind several substrate molecules and thus often exhibits a complex pattern of drug-drug interactions. In order to better understand structural and functional aspects of binding of multiple substrate molecules to CYP3A4 we used resonance Raman and UV-VIS spectroscopy to document the effects of binding of synthetic testosterone dimers of different configurations, cis-TST(2) and trans-TST(2). We directly demonstrate that the binding of two steroid molecules, which can assume multiple possible configurations inside the substrate binding pocket of monomeric CYP3A4, can lead to active site structural changes that affect functional properties. Using resonance Raman spectroscopy, we have documented perturbations in the ferric and ferrous – CO bound states by these substrates, and compared these results with effects caused by binding of monomeric TST. While the binding of trans-TST(2) yields results which are similar to those obtained with saturating amounts of monomeric TST, the binding of cis-TST(2) is much tighter and results in significantly more pronounced conformational changes of the porphyrin side chains and Fe-CO unit. In addition, binding of an additional monomeric TST molecule in the remote allosteric site significantly improves binding affinity and the overall spin shift for CYP3A4 with trans-TST(2) dimer bound inside the substrate binding pocket. This result provides the first direct evidence for an allosteric effect of the peripheral binding site at the protein – membrane interface on the functional properties of CYP3A4.